A STUDY OF ECOTOURISM POTENTIAL IN MANGROVE FOREST AT MENDALOK VILLAGE SUNGAI KUNYIT SUBDISTRICT MEMPAWAH REGENCY - muchri insiardi; Inpurwanto Inpurwanto; Ahmad Mulyadi (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT Mangrove forests in Mendalok Village have an area of 6 ha and ± 500 m2 which have been managed by BUMDes as mangrove tourism, which is named Polaria Tanjungpagar. This study aims to determine the potential of mangrove ecotourism seen from the perceptions, motivations of the society and visitors, knowing the density of the type of mangrove forest vegetation and knowing the suitability of mangrove ecotourism. This research was conducted from July-December 2018 in the mangrove forest area of Mendalok Village, Sungai Kunyit Subdistrict, Mempawah Regency, using survey, literature study and interview methods. The analysis of the data used in this research was the percentage of perception, motivations of society and visitors, tourist suitability analysis, analysis of attractions of ecotourism activities, analysis of regional carrying capacity and density analysis of mangrove vegetation. The results of the research on mangrove forests in Mendalok Village have ecotourism potential in the form of a high level of community participation for ecotourism activities of 83.33%, having the potential of mangrove resources for ecotourism development in the form of 12 species of mangroves that make the area suitable for ecotourism. The level of mangrove density in trees is classified as medium with a value of 1011.12 ind / ha, the level of saplings and seedlings is classified as a value of 12755.56 ind / ha and 38257.78 ind / ha which means that it has good regenersion and is suitable for ecotourism. Ecotourism suitability index in the area of organic waste flow with a very suitable category (SS), ecotourism areas have a very suitable category (SS) and unmanaged areas have conditional appropriate categories then the carrying capacity of Tanjungpagar Polaria mangrove area can only accommodate 40 tourists person / day. Based on the research findings of mangrove forests in Mendalok Village, it has the potential to be used as ecotourism. Keywords: Ecotourism, Potency, Mangrove